A high temperature resistant ceramic body material and preparation method thereof

By using calcined kaolin, quartz, aluminum carbosilicide, dolomite, magnesium-aluminum spinel and zirconium bored in ceramic bodies, and combining modified barium phenolic resin to form a dense oxide layer and glassy filler, the solution is solved The problem of high-temperature calcination of ceramic blanks is prone to deformation, which significantly improves the high-temperature deformation performance and structural stability of ceramic blanks.

CN119019152BActive Publication Date: 2025-01-07ZI BO SHI WANG TAO CI YOU XIAN GONG SI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411516272.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-07
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

Ceramic blanks are prone to deformation during high-temperature roasting, resulting in structural instability, and the prior art is difficult to effectively solve this problem.

Method used

Use specific formulas of ceramic blank materials, including calcined kaolin, quartz, aluminum carbosilicide, dolomite, magnesium-aluminum spinel and zirconium bored, and form dense alumina oxide layers and glass by strictly controlling the raw material composition and process steps. Boron oxide is combined with modified barium phenolic resin as a binding agent to improve the high-temperature structure and performance stability of the ceramic body.

Benefits of technology

It significantly improves the deformation performance and structural stability of the ceramic body at high temperature, ensures that the ceramic body is not prone to volume shrinkage and internal stress during the high-temperature firing process, and improves the mechanical and thermal properties of the ceramic body.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high temperature resistant ceramic body material and a preparation method thereof, belonging to the technical field of ceramic production. First, the high temperature resistant ceramic body material comprises the following raw materials by weight: 30-40 parts of calcined kaolin, 20-25 parts of quartz, 15-20 parts of dolomite, 12-15 parts of zirconium boride, 10-12 parts of aluminum carbon silicide, 8-10 parts of binder and 5-8 parts of magnesium aluminum spinel. Then, the preparation method comprises the following steps: mixing the above raw materials and placing them in a ball mill to obtain a body slurry, drying the body slurry to a water content of 1% to 3%, and obtaining a high temperature resistant ceramic body material. The ceramic body material of the invention is composed of calcined kaolin, quartz, aluminum carbon silicide, dolomite, magnesium aluminum spinel, zirconium boride and a binder. The invention strictly controls the composition and dosage of the raw materials, and after testing, the ceramic body material finally prepared has excellent performance of high temperature resistant body deformation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic production, and in particular relates to a high temperature resistant ceramic blank material and a preparation method thereof. Background Art

[0002] During the calcination process of ceramic production, the chemical composition of the ceramic body raw materials has a significant impact on the deformation of the body during calcination. For example, raw materials such as kaolin, feldspar and quartz will undergo physical and chemical changes during heating, resulting in uneven volume shrinkage / expansion, which will cause deformation.

[0003] In order to solve the technical problem that ceramic green bodies are prone to deformation during high-temperature sintering, the Chinese invention patent with application number 201710121242.X discloses a high-temperature resistant deformation Jingdezhen traditional ceramic green body and its preparation method. This invention patent increases the high-temperature structural strength of the green body by adding alumina powder to the traditional green body material and forming high-modulus corundum and mullite phases through high-temperature sintering. The present invention aims to further improve the formula of ceramic green bodies on the basis of the existing technology, aiming to further improve the high-temperature deformation resistance of green body materials during calcination. Summary of the invention

[0004] The object of the present invention is to provide a high temperature resistant ceramic body material and a preparation method thereof, so as to solve the technical problem that the ceramic body is prone to deformation during high temperature sintering.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A high temperature resistant ceramic body material, comprising the following raw materials in parts by weight:

[0007] 30-40 parts of calcined kaolin;

[0008] 20-25 parts of quartz;

[0009] 15-20 parts of dolomite;

[0010] Zirconium boride 12-15 parts;

[0011] 10-12 parts of aluminum carbide;

[0012] 8-10 parts of binder;

[0013] 5 to 8 parts of magnesium aluminum spinel.

[0014] Furthermore, the high temperature resistant ceramic body material comprises the following raw materials in parts by weight:

[0015] 35 parts of calcined kaolin;

[0016] quartz 24 parts;

[0017] 18 parts of dolomite;

[0018] Zirconium boride 14 parts;

[0019] Aluminium carbide 12 parts;

[0020] 10 parts of binder;

[0021] 7 parts of magnesium aluminum spinel.

[0022] Furthermore, the aluminum carbon silicide is prepared by the following steps:

[0023] Aluminum powder, silicon powder and carbon black were added to the ball mill. After the addition was completed, the ball milling was carried out for 24 hours. After the ball milling was completed, it was placed in a nitrogen environment at 100°C and dried for 12 hours. Then, it was placed in a vacuum calcining furnace for calcining, and then cooled to room temperature with the furnace to obtain aluminum carbide.

[0024] Furthermore, the mass ratio of the aluminum powder, silicon powder and carbon black is 4:1:4.

[0025] Furthermore, in the ball milling process: the ball milling medium is a silicon carbide ball milling ball with a diameter of 5 mm, the ball-to-material ratio is 8 to 10:1, and the ball mill speed is 150 to 200 r / min.

[0026] Furthermore, the calcination process: firstly, the temperature is raised from room temperature to 1200°C at 10°C / min, then raised to 1450°C at 5°C / min, and then raised to 1500°C at 2°C / min, and calcined at a constant temperature for 5 to 6 hours.

[0027] Furthermore, the binding agent is prepared by the following steps:

[0028] Add KH-560, barium phenolic resin and Amberlyst-15 ion exchange resin to a stirring kettle, stir at room temperature for 10 to 20 minutes, then heat to 40 to 50°C, and stir at constant temperature for 24 hours. After completion, cool to room temperature, filter out the Amberlyst-15 ion exchange resin, and obtain a binder.

[0029] Furthermore, the mass ratio of the KH-560, barium phenolic resin and Amberlyst-15 ion exchange resin is 1:10:0.5-1.

[0030] Furthermore, the method for preparing the high temperature resistant ceramic body material comprises the following steps:

[0031] Calcined kaolin, quartz, aluminum silicide, dolomite, magnesium aluminum spinel, zirconium boride and binder are weighed according to mass parts, mixed and placed in a ball mill, and then ball milling media and water accounting for 60% to 75% of the total mass of the green body raw materials are added to the ball mill. The ball milling is continued for 12 to 24 hours. After the ball milling is completed, a green body slurry is obtained. The green body slurry is dried to a water content of 1% to 3% to obtain a high temperature resistant ceramic green body material.

[0032] Furthermore, in the ball milling process: the ball milling medium is a silicon carbide ball with a diameter of 5 mm, the ball-to-material ratio is 5:1, the ball mill speed is 50-60 r / min, and the ball milling is performed by alternating forward rotation for 15 minutes and reverse rotation for 15 minutes.

[0033] Beneficial effects of the present invention:

[0034] The present invention provides a ceramic body material and a preparation method thereof. The ceramic body material of the present invention is composed of calcined kaolin, quartz, aluminum carbon silicide, dolomite, magnesium aluminum spinel, zirconium boride and a binder. The present invention strictly controls the composition and amount of raw materials. After testing, the finally prepared ceramic body material has excellent performance of high temperature body deformation resistance. The specific principle is as follows:

[0035] First, during the calcination process of the ceramic green body material prepared by the present invention:

[0036] When the temperature rises from room temperature to the low temperature section of 1000°C, in the initial stage of calcination, the ceramic body material will undergo dehydration and decomposition reactions, and free water and crystal water will be gradually removed. When the calcination temperature reaches 700-900°C, the dolomite in the ceramic body material will gradually decompose into carbon dioxide, calcium oxide and magnesium oxide. When the calcination temperature reaches 900-1000°C, the aluminum silicide (Al4SiC4) prepared by the present invention in the ceramic body material will gradually undergo an oxidation reaction, and the oxidation process will gradually form a dense aluminum oxide layer and silicon dioxide. As the temperature rises, the thickness of the aluminum oxide layer gradually increases. The aluminum oxide layer can prevent air from diffusing into the interior of the ceramic body material, effectively protecting the remaining components in the ceramic body material from further oxidation, thereby helping to improve the stability of the structure and performance of the ceramic body material at high temperatures.

[0037] When the calcination temperature reaches the medium temperature range of 1000-1400°C, the zirconium boride (ZrB2) in the ceramic body material will gradually undergo an oxidation reaction. Specifically: First, within the temperature range of 1000-1180°C, the zirconium boride will gradually undergo oxidation to generate zirconium oxide and glassy boron oxide. The glassy boron oxide can penetrate into the pores formed by burnout in the ceramic body material to fill them, thereby improving the stability of the ceramic body structure and performance in the medium temperature range. At the same time, boron oxide can decompose dolomite and react with magnesium oxide in magnesia-aluminum spinel to generate magnesium borate with a low melting point (988°C). In addition, excess boron oxide can also react with the pores in the ceramic body material that have been burnt out. The water vapor formed in the process reacts with the calcium oxide produced by the decomposition of dolomite to synthesize low-melting-point calcium borate (450°C). The magnesium borate and calcium borate formed in the medium-temperature stage can further fill the pores inside the high-thermal-conductivity composite material, thereby more effectively improving the stability of the structure and performance of the ceramic body material at high temperatures. Then, when the calcination temperature is further increased to 1400°C, the zirconium oxide reacts with the silicon dioxide in the quartz / calcined kaolin / aluminum carbon silicide to synthesize zircon quartz. The synthesis of zircon quartz is accompanied by volume expansion, which can offset the internal stress and voids caused by the volume shrinkage caused by the burning loss of the ceramic body during the calcination process, thereby further ensuring the stability of the structure and performance of the ceramic body in the high-temperature stage.

[0038] When the calcination temperature reaches the high temperature range of 1600-1700°C, the silica and alumina in the ceramic body material (silicon dioxide / alumina in calcined kaolin, silicon dioxide in quartz and siliconized aluminum carbide produced by oxidation) gradually generate mullite. Mullite has excellent mechanical and thermal properties at high temperatures, which can ensure the stability of the structure and performance of the ceramic body in the high temperature range. At the same time, the synthesis of mullite is also accompanied by volume expansion, which can offset the internal stress and voids caused by the volume shrinkage caused by the burning of the ceramic body during the calcination process, and ensure the stability of the structure and performance of the ceramic body in the high temperature range.

[0039] Finally, a binder is added to the ceramic body material of the present invention, and the binder is KH-560 modified barium phenolic resin. The barium phenolic resin has excellent heat resistance, but its toughness is poor and its shrinkage rate is large after curing. Therefore, the present invention improves the flexibility of the barium phenolic resin by introducing silicon-oxygen bonds into the barium phenolic resin. At the same time, the introduction of silicon-oxygen bonds helps to improve the bonding strength between the binder and the remaining raw materials of the ceramic body and between the raw materials, thereby improving the internal density of the finally prepared ceramic body material, and ultimately helping to improve the stability of the structure and performance of the ceramic body. DETAILED DESCRIPTION

[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Example 1

[0042] Preparation of aluminum silicon carbide:

[0043] Aluminum powder (metal aluminum powder, 100 mesh, purchased from Hunan Jinhao New Materials Technology Co., Ltd.), silicon powder (purity 99%, 200 mesh, purchased from Beijing October New Materials Technology Co., Ltd.) and carbon black (N330 wet process carbon black, purchased from Jinan Zhongbei Fine Chemical Co., Ltd.) were added to the ball mill in a mass ratio of 4:1:4. After the addition was completed, the ball milling treatment was carried out for 24 hours, wherein the ball milling medium was a silicon carbide ball milling ball with a diameter of 5 mm, the ball-to-material ratio was 8:1, and the ball mill speed was 1500r / min. After the ball milling was completed, it was placed under nitrogen conditions at 100°C and dried for 12 hours, and then placed in a vacuum calcining furnace for calcination treatment, firstly heated from room temperature to 1200°C at 10°C / min, then heated to 1450°C at 5°C / min, and then heated to 1500°C at 2°C / min, calcined at a constant temperature for 5 hours, and then cooled to room temperature with the furnace to obtain carbon silicon aluminum.

[0044] Example 2

[0045] Preparation of aluminum silicon carbide:

[0046] Aluminum powder (metal aluminum powder, 100 mesh, purchased from Hunan Jinhao New Materials Technology Co., Ltd.), silicon powder (purity 99%, 200 mesh, purchased from Beijing October New Materials Technology Co., Ltd.) and carbon black (N330 wet process carbon black, purchased from Jinan Zhongbei Fine Chemical Co., Ltd.) were added to the ball mill in a mass ratio of 4:1:4. After the addition was completed, the ball milling treatment was carried out for 24 hours, wherein the ball milling medium was a silicon carbide ball with a diameter of 5 mm, the ball-to-material ratio was 9:1, and the ball mill speed was 180 r / min. After the ball milling was completed, it was placed under nitrogen conditions at 100°C and dried for 12 hours, and then placed in a vacuum calcining furnace for calcination treatment, firstly heated from room temperature to 1200°C at 10°C / min, then heated to 1450°C at 5°C / min, and then heated to 1500°C at 2°C / min, calcined at a constant temperature for 6 hours, and then cooled to room temperature with the furnace to obtain carbon silicon aluminum.

[0047] Example 3

[0048] Preparation of aluminum silicon carbide:

[0049] Aluminum powder (metal aluminum powder, 100 mesh, purchased from Hunan Jinhao New Materials Technology Co., Ltd.), silicon powder (purity 99%, 200 mesh, purchased from Beijing October New Materials Technology Co., Ltd.) and carbon black (N330 wet process carbon black, purchased from Jinan Zhongbei Fine Chemical Co., Ltd.) were added to the ball mill in a mass ratio of 4:1:4. After the addition was completed, the ball milling treatment was carried out for 24 hours, wherein the ball milling medium was a silicon carbide ball with a diameter of 5 mm, the ball-to-material ratio was 10:1, and the ball mill speed was 200r / min. After the ball milling was completed, it was placed under nitrogen conditions at 100°C and dried for 12 hours, and then placed in a vacuum calcining furnace for calcination treatment, firstly heated from room temperature to 1200°C at 10°C / min, then heated to 1450°C at 5°C / min, and then heated to 1500°C at 2°C / min, calcined at a constant temperature for 6 hours, and then cooled to room temperature with the furnace to obtain carbon silicon aluminum.

[0050] Example 4

[0051] Preparation of binding agent:

[0052] KH-560 (98%, Sinopharm Chemical Reagent Co., Ltd.), barium phenolic resin (industrial grade, Beijing Fiberglass Research and Design Institute Co., Ltd.) and Amberlyst-15 ion exchange resin (purchased from Sinopharm Chemical Reagent Co., Ltd.) were added to a stirring kettle in a mass ratio of 1:10:0.5, and stirred at room temperature for 10 minutes. The stirring kettle was then heated to 40°C and stirred at a constant temperature for 24 hours. After completion, it was cooled to room temperature, and the Amberlyst-15 ion exchange resin was filtered out to obtain a binder.

[0053] Example 5

[0054] Preparation of binding agent:

[0055] KH-560 (98%, Sinopharm Chemical Reagent Co., Ltd.), barium phenolic resin (industrial grade, Beijing Fiberglass Research and Design Institute Co., Ltd.) and Amberlyst-15 ion exchange resin (purchased from Sinopharm Chemical Reagent Co., Ltd.) were added to a stirring kettle in a mass ratio of 1:10:1, and stirred at room temperature for 20 minutes. The stirring kettle was then heated to 50°C and stirred at a constant temperature for 24 hours. After completion, it was cooled to room temperature, and the Amberlyst-15 ion exchange resin was filtered out to obtain a binder.

[0056] Example 6

[0057] Preparation of binding agent:

[0058] KH-560 (98%, Sinopharm Chemical Reagent Co., Ltd.), barium phenolic resin (industrial grade, Beijing Fiberglass Research and Design Institute Co., Ltd.) and Amberlyst-15 ion exchange resin (purchased from Sinopharm Chemical Reagent Co., Ltd.) were added to a stirring kettle in a mass ratio of 1:10:0.8, and stirred at room temperature for 20 minutes. The stirring kettle was then heated to 50°C and stirred at a constant temperature for 24 hours. After completion, it was cooled to room temperature, and the Amberlyst-15 ion exchange resin was filtered out to obtain a binder.

[0059] Example 7

[0060] Preparation of high temperature resistant ceramic body materials:

[0061] First, the high temperature resistant ceramic body material includes the following raw materials by weight:

[0062] 30 parts of calcined kaolin;

[0063] Quartz 20 parts;

[0064] 15 parts of dolomite;

[0065] Zirconium boride 12 parts;

[0066] 10 parts of aluminum carbosilicide prepared in Example 1;

[0067] 8 parts of the binder prepared in Example 4;

[0068] 5 parts of magnesium aluminum spinel.

[0069] Then, the preparation method of the high temperature resistant ceramic body material comprises the following steps:

[0070] The raw materials calcined kaolin, quartz, aluminum carbon silicide prepared in Example 1, dolomite, magnesium aluminum spinel, zirconium boride and binder prepared in Example 4 were weighed according to their mass parts, wherein calcined kaolin was purchased from Shanxi Chaopai Calcined Kaolin Co., Ltd. (brand name DG25BA), quartz was purchased from Shanghai Chuangyu Chemical New Materials Co., Ltd. (purity 98%), dolomite was purchased from Shandong Chenhua Mining Co., Ltd., magnesium aluminum spinel was purchased from Shandong Hengjia High Purity Aluminum Technology Co., Ltd., and zirconium boride was purchased from Sinopharm Chemical Reagent Co., Ltd. ( Purity 99%), after weighing, mix and place in a ball mill, then add ball milling medium and water of 75% of the total mass of the green body raw materials into the ball mill, wherein the ball milling medium is a silicon carbide ball milling ball with a diameter of 5 mm, and the ball-to-material ratio is 5:1, and then adjust the speed of the ball mill to 50r / min, and adopt a ball milling method of alternating forward rotation for 15min and reverse rotation for 15min during ball milling, and continue ball milling for 12h. After ball milling, a green body slurry is obtained, and the green body slurry is dried to a water content of 3% to obtain a high temperature resistant ceramic green body material.

[0071] Example 8

[0072] Preparation of high temperature resistant ceramic body materials:

[0073] First, the high temperature resistant ceramic body material includes the following raw materials by weight:

[0074] 35 parts of calcined kaolin;

[0075] quartz 24 parts;

[0076] 18 parts of dolomite;

[0077] Zirconium boride 14 parts;

[0078] 12 parts of aluminum carbosilicide prepared in Example 2;

[0079] 10 parts of the binder prepared in Example 5;

[0080] 7 parts of magnesium aluminum spinel.

[0081] Then, the preparation method of the high temperature resistant ceramic body material comprises the following steps:

[0082] The raw materials calcined kaolin, quartz, aluminum carbosilicide prepared in Example 2, dolomite, magnesium aluminum spinel, zirconium boride and binder prepared in Example 5 were weighed according to their mass parts, wherein calcined kaolin was purchased from Shanxi Chaopai Calcined Kaolin Co., Ltd. (brand name DG25BA), quartz was purchased from Shanghai Chuangyu Chemical New Materials Co., Ltd. (purity 98%), dolomite was purchased from Shandong Chenhua Mining Co., Ltd., magnesium aluminum spinel was purchased from Shandong Hengjia High Purity Aluminum Technology Co., Ltd., and zirconium boride was purchased from Sinopharm Chemical Reagent Co., Ltd. (pure The mixture is weighed, mixed and placed in a ball mill, and then the ball milling medium and 65% of the total mass of the green body raw materials are added to the ball mill, wherein the ball milling medium is a silicon carbide ball milling ball with a diameter of 5 mm, and the ball-to-material ratio is 5:1. The speed of the ball mill is adjusted to 60 r / min, and the ball milling is carried out by alternating forward rotation for 15 min and reverse rotation for 15 min. The ball milling is continued for 24 hours. After the ball milling is completed, a green body slurry is obtained, and the green body slurry is dried to a water content of 1.5% to obtain a high temperature resistant ceramic green body material.

[0083] Example 9

[0084] Preparation of high temperature resistant ceramic body materials:

[0085] Preparation of high temperature resistant ceramic body materials:

[0086] First, the high temperature resistant ceramic body material includes the following raw materials by weight:

[0087] 40 parts of calcined kaolin;

[0088] Quartz 25 parts;

[0089] 20 parts of dolomite;

[0090] Zirconium boride 15 parts;

[0091] 12 parts of aluminum carbosilicide prepared in Example 3;

[0092] 10 parts of the binder prepared in Example 6;

[0093] 8 parts of magnesium aluminum spinel.

[0094] Then, the preparation method of the high temperature resistant ceramic body material comprises the following steps:

[0095] The raw materials calcined kaolin, quartz, aluminum carbosilicide prepared in Example 3, dolomite, magnesium aluminum spinel, zirconium boride and binder prepared in Example 6 were weighed according to their mass parts, wherein calcined kaolin was purchased from Shanxi Chaopai Calcined Kaolin Co., Ltd. (brand name DG25BA), quartz was purchased from Shanghai Chuangyu Chemical New Materials Co., Ltd. (purity 98%), dolomite was purchased from Shandong Chenhua Mining Co., Ltd., magnesium aluminum spinel was purchased from Shandong Hengjia High Purity Aluminum Technology Co., Ltd., and zirconium boride was purchased from Sinopharm Chemical Reagent Co., Ltd. ( Purity 99%), after weighing, mix and place in a ball mill, then add ball milling medium and 60% of the total mass of green body raw materials into the ball mill, wherein the ball milling medium is silicon carbide ball milling balls with a diameter of 5 mm, and the ball-to-material ratio is 5:1, and then adjust the speed of the ball mill to 60r / min, and adopt a ball milling method of alternating forward rotation for 15min and reverse rotation for 15min during ball milling, and continue ball milling for 24h. After ball milling, green body slurry is obtained, and the green body slurry is dried to a water content of 1% to obtain a high temperature resistant ceramic green body material.

[0096] Comparative Example 1

[0097] Comparative Example 1 is the control group of Example 8, in which the aluminum carbide prepared in Example 2 is removed from the raw materials in Example 8, and the remaining raw materials, raw material amounts and preparation methods are kept the same as those in Example 8, and finally a high-temperature resistant ceramic green body material is obtained.

[0098] Comparative Example 2

[0099] Comparative Example 2 is the control group of Example 8, in which zirconium boride in the raw materials in Example 8 is removed, and the remaining raw materials, raw material amounts and preparation methods are kept the same as in Example 8, and finally a high temperature resistant ceramic green body material is obtained.

[0100] Comparative Example 3

[0101] Comparative Example 3 is the control group of Example 8, in which the binder prepared in Example 5 in the raw materials in Example 8 is replaced with the raw material barium phenolic resin in Example 5, and the remaining raw materials, raw material amounts and preparation methods are the same as those in Example 8, and finally a high-temperature resistant ceramic green body material is obtained.

[0102] The performance test was performed on the high temperature resistant ceramic green body materials prepared in Examples 7 to 9 and Comparative Examples 1 to 3. The performance test process is as follows, and the test results are shown in Table 1:

[0103] Heating permanent line change (%): Referring to the heating permanent change test method for dense shaped refractory products in GB / T5988-2022 "Test method for heating permanent line change of refractory materials", a rectangular specimen (length 50mm×width 50mm×height 60mm) of high-temperature resistant ceramic green body material is heated, first from room temperature to 1200℃ at 10℃ / min, then to 1650℃ at 5℃ / min, and then to 1700℃ at 2℃ / min, kept at constant temperature for 6h, and then naturally cooled to room temperature to obtain a ceramic product. Referring to the calculation formula of 8.1 heating permanent line change in the standard, the heating permanent line change (%) is measured, and a single group of embodiments / comparative examples is tested five times, and the five test results are taken and the average value is calculated. The results are shown in Table 1 below.

[0104] Mohs hardness: The Mohs hardness of ceramic products is obtained by testing the heating permanent line change detection process using the American Mineralab Mohs hardness tester.

[0105] Compressive strength (MPa): The compressive strength of ceramic products obtained during the heating permanent line change detection process was tested using a CMT6104 electronic universal testing machine.

[0106] Table 1 Test results

[0107] project Example 7 Example 8 Example 9 Comparative Example 1 Comparative Example 2 Comparative Example 3 Heating permanent line change (%) 0.64 0.51 0.55 1.10 1.32 0.87 Mohs hardness 8 8 8 8 7 7 Compressive strength(MPa) 112.3 115.7 114.0 96.4 82.5 105.8

[0108] It can be seen from Table 1 that the high temperature resistant ceramic green body materials prepared in Examples 7 to 9 of the present invention have excellent high temperature deformation resistance, and at the same time, the ceramic products after calcination have excellent mechanical properties.

[0109] It should be noted that, in this article, terms such as "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or equipment that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment.

[0110] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high temperature resistant ceramic body material, characterized in that: Including the following raw materials by weight: 30-40 parts of calcined kaolin; 20-25 parts of quartz; 15-20 parts of dolomite; Zirconium boride 12-15 parts; 10-12 parts of aluminum carbide; 8-10 parts of binder; 5-8 parts of magnesium aluminum spinel; The aluminum silicide is prepared by the following steps: Aluminum powder, silicon powder and carbon black were added to a ball mill. After the addition was completed, the ball milling was performed for 24 hours. After the ball milling was completed, the ball milling was placed under nitrogen conditions at 100° C. and dried for 12 hours. The ball milling was then placed in a vacuum calcining furnace for calcining. The ball milling was then cooled to room temperature to obtain aluminum carbide. The calcination process is as follows: firstly, the temperature is raised from room temperature to 1200°C at 10°C / min, then to 1450°C at 5°C / min, and then to 1500°C at 2°C / min, and the calcination is carried out at a constant temperature for 5 to 6 hours; The binding agent is prepared by the following steps: Add KH-560, barium phenolic resin and Amberlyst-15 ion exchange resin to a stirred kettle, stir at room temperature for 10 to 20 minutes, then heat to 40 to 50° C., and stir at constant temperature for 24 hours. After completion, cool to room temperature, filter and remove the Amberlyst-15 ion exchange resin to obtain a binder; The mass ratio of the KH-560, barium phenolic resin and Amberlyst-15 ion exchange resin is 1:10:0.5-1.

2. A high temperature resistant ceramic body material according to claim 1, characterized in that: Including the following raw materials by weight: 35 parts of calcined kaolin; quartz 24 parts; 18 parts of dolomite; Zirconium boride 14 parts; Aluminium carbide 12 parts; 10 parts of binder; 7 parts of magnesium aluminum spinel.

3. A high temperature resistant ceramic body material according to claim 1, characterized in that: The mass ratio of the aluminum powder, silicon powder and carbon black is 4:1:

4.

4. A high temperature resistant ceramic body material according to claim 1, characterized in that: In the ball milling process, the ball milling medium is a silicon carbide ball with a diameter of 5 mm, the ball-to-material ratio is 8 to 10:1, and the ball mill speed is 150 to 200 r / min.

5. A method for preparing a high temperature resistant ceramic body material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Calcined kaolin, quartz, aluminum silicide, dolomite, magnesium aluminum spinel, zirconium boride and binder are weighed according to mass parts, mixed and placed in a ball mill, and then ball milling media and water accounting for 60% to 75% of the total mass of the green body raw materials are added to the ball mill. The ball milling is continued for 12 to 24 hours. After the ball milling is completed, a green body slurry is obtained. The green body slurry is dried to a water content of 1% to 3% to obtain a high temperature resistant ceramic green body material.

6. The method for preparing a high temperature resistant ceramic body material according to claim 5, characterized in that: During the ball milling process, the ball milling medium is a silicon carbide ball with a diameter of 5 mm, the ball-to-material ratio is 5:1, the ball mill speed is 50-60 r / min, and the ball milling is performed by alternating forward rotation for 15 minutes and reverse rotation for 15 minutes.

Citation Information

Patent Citations

  • High-temperature deformation-resistant Jingdezhen traditional ceramic body and preparation method thereof

    CN106866108A

  • Antioxidant low-carbon magnesia carbon brick and preparation process thereof

    CN118515470A

  • Rare earth-containing ceramic grinding ball and preparation method thereof

    CN118771883A